(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article is concerned with the usage and application of stories in preliminary education in order to develop oral speech of children in foreign languages, especially in English. The authors discuss and provide comparison and analysis of the ways in which stories in different genres can be implemented in practice and what sorts of activities can be used for each type of genre.